2015
DOI: 10.1103/physreva.91.062105
|View full text |Cite
|
Sign up to set email alerts
|

Modified weak measurements for the detection of the photonic spin Hall effect

Abstract: Weak measurement is an important technique for the detection of the tiny spin-dependent splitting in photonic spin Hall effect. The weak measurement is only valid when the probe wave function remains almost undisturbed during the procedure of measurements. However, it does not always satisfy such condition in some practical situations, such as in the strong-coupling regime or when the preselected and postselected states are nearly orthogonal. In this paper, we develop a modified weak measurement for the detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 76 publications
(125 reference statements)
1
33
0
Order By: Relevance
“…In the experiments, the resolution of displacement reaches ~1 Å. In fact, recent research has shown that the maximum weak value and pointer shift could be acquired with an optimal superposition of pre-selection and post-selection states, which offers a possible way to improve the accuracy of weak measurements [128][129][130][131].…”
Section: Weak Measurements Of the She Of Lightmentioning
confidence: 99%
“…In the experiments, the resolution of displacement reaches ~1 Å. In fact, recent research has shown that the maximum weak value and pointer shift could be acquired with an optimal superposition of pre-selection and post-selection states, which offers a possible way to improve the accuracy of weak measurements [128][129][130][131].…”
Section: Weak Measurements Of the She Of Lightmentioning
confidence: 99%
“…In order to study the small phase difference between L- and R-circular polarized light caused by different optical medium, we transform the linear polarization eigenstates into circular polarized eigenstates by the following relations [ 23 , 24 ] where , , , and represent the eigenstates of horizontal linear polarized light, verticallinear polarized light, right circular polarized light, and left circular polarized light, respectively. The pre- and post-selecting polarization states can be represented by circular polarized light as …”
Section: Theorymentioning
confidence: 99%
“…But in fact the shift has a maximum value when the postselected angle is close to zero. Under this situation, a modified weak measurements is required [54].…”
Section: Quantum Weak Value Amplificationmentioning
confidence: 99%